A novel domino approach for synthesis of indolyl tetrahydropyrano[4, 3-c]pyrazole derivatives as anticancer agents. Issue 38 (22nd September 2016) - Wang, Fu-Qiang; Yang, Hui; He, Bin; Jia, Yong-Kang; Meng, Shi-Yao; Zhang, Chao; Liu, Hong-Min; Liu, Feng-Wu
Abstract: A series of indolyl substituted 1, 4, 6, 7-tetrahydropyrano[4, 3- c ]pyrazole derivatives were synthesized via a domino method based on the 1, 4:3, 6-Dianhydrofructose. The mechanism was proposed and proved by calculation with a density functional theory (DFT), which includes formation of phenylhydrazone, furanone ring opening, Fischer indole synthesis, pyrazole ring closing and a furan ring expansion. In vitro antitumor activity of all synthesized compounds against four human cancer cell lines (MCF-7, EC-109, HGC-27, and PC-3 cell lines) were then evaluated, using MTT assay. We found that most of the compounds were more potent than the positive control 5-fluorouracil. Particularly, compound4i against HGC-27 and PC-3, 4j against EC-109 cell lines showed three fold greater activity than 5-fluorouracil, respectively. The activity of compounds4c and4d against MCF-7 cell line was close to that of doxorubicin. Graphical abstract: